Faktor yang Mempengaruhi Pengambilan Keputusan Investasi Cryptocurrency - Ervina Febrianti; M. Rifki Bakhtiar (UniSadhuGuna Business School, 2024)
This research was used to measure the influence of investment knowledge, return, risk tolerance, financial literacy, regret aversion, and overconfidence on cryptocurrency investment decisions. This research is quantitative research where the objects used are the public or active investors who invest in cryptocurrency in Indonesia. The number of samples used in this research was 101 respondents. Data collection techniques use questionnaires and data processing and hypothesis testing using Spss. The results of this research explain that the variables investment knowledge, return, risk tolerance have a positive but not significant effect on cryptocurrency investment decisions. Meanwhile, financial literacy, regret aversion, overconfidence have a significant positive effect on cryptocurrency investment decisions.